Evaluasi Model Kematangan E-Government pada Layanan Publik Kecamatan di Indonesia Menggunakan Framewok SPBE - I Made Sukarsa; Ida Bagus Ananda Paramartha; Anak Agung Ketut Agung Cahyawan; Kadek Suar Wibawa; Putu Gede Arya Sumertha Yasa; Ni Made Swasti Wulanyani; Ni Wayan Wisswani (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The administration of Indonesian public services has entered the era of Industrial Revolution 4.0, which is a collaborative phase, requiring that every public service implement a service system base on digitization and integrated. The public service that has always been an open discussion is the PATEN Sub-District service. PATEN is a public service system that facilitates community access to get assistance related to population and licensing issues through the Sub-District. Based on PANRB Ministerial Regulation No. 5 of 2018 concerning SPBE Guidelines. SPBE is the framework of the Indonesian Government's Maturity Model, which assesses the level of maturity index in Local Government services. SPBE implementation only stops at the District level and has not touched the Sub-District level, so the SPBE research conducted on public services in the Sub-District. SPBE maturity evaluation has been re-mapped in public services so that not all domains and indicators used. Based on the SPBE mapping results, it produces two domains and four indicators that will use as an assessment of maturity. The data collection method used was a questionnaire. The results showed the evaluation of the maturity of the SPBE in public services in the Sub-District obtained a “Poor” category with a total index value of 1.47. Accordingly, it was necessary to provide recommendations and improvement strategies to increase the value of the SPBE index.